2017
DOI: 10.1001/jamaneurol.2017.1912
|View full text |Cite|
|
Sign up to set email alerts
|

Neurological Complications Associated With Anti–Programmed Death 1 (PD-1) Antibodies

Abstract: IMPORTANCE Neurological complications are an increasingly recognized consequence of the use of anti-programmed death 1 (PD-1) antibodies in the treatment of solid-organ tumors, with an estimated frequency of 4.2%. To date, the clinical spectrum and optimum treatment approach are not established.OBJECTIVE To investigate the frequency, clinical spectrum, and optimum treatment approach to neurological complications associated with anti-PD-1 therapy. DESIGN, SETTING, AND PARTICIPANTSThis single-center, retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
213
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(217 citation statements)
references
References 22 publications
2
213
0
2
Order By: Relevance
“…In addition, we discovered other single cases of very rare AEs in our cohort. Cases of rhabdomyolysis [21] or Guillain-Barré syndrome [22] following nivolumab treatment have already been reported, but these are known neurological complications of PD-1 antibodies and rare AEs of immunotherapy treatment [23]. Many results concerning safety data between the phase 3 study of Brahmer et al [10] and our study are similar; however, the frequency of severe AEs was different.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, we discovered other single cases of very rare AEs in our cohort. Cases of rhabdomyolysis [21] or Guillain-Barré syndrome [22] following nivolumab treatment have already been reported, but these are known neurological complications of PD-1 antibodies and rare AEs of immunotherapy treatment [23]. Many results concerning safety data between the phase 3 study of Brahmer et al [10] and our study are similar; however, the frequency of severe AEs was different.…”
Section: Discussionsupporting
confidence: 65%
“…Although neurological irAEs (irAE‐Ns) are rare, they can be severe and even fatal. Although short courses of prednisone started after ICI infusion do not appear to reverse the antitumor effect of the ICI, the influence of immunosuppression for irAEs or longer courses of steroids on cancer outcomes remains unknown . Clinical phenotypes, including encephalitis, neuropathies, myasthenia gravis (MG), and myositis, are described in small case series or case reports .…”
mentioning
confidence: 99%
“…Clinical phenotypes, including encephalitis, neuropathies, myasthenia gravis (MG), and myositis, are described in small case series or case reports . However, these reports have generally been limited to single malignancies (melanoma) and/or ICI class (anti–PD‐1 antibodies) . Other studies have reported clinical presentation of MG among patients treated with either nivolumab or ipilimumab monotherapy utilizing pharmaceutical company postmarketing surveillance databases .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,11 Neurologic complications of checkpoint inhibitor therapies are also increasingly recognized, including headache, seizures, cranial neuropathies, and polyneuropathy. 12 A recent report 13 found that 2.9% of a 347-patient cohort treated with anti-PD1 therapy developed neurologic complications (predominantly myopathies and neuropathies). Cerebral vasculitis has been reported as a result of PD-1 inhibition in a recent case report.…”
Section: Discussionmentioning
confidence: 99%